Digitalization of South Ostrobothnian companies - Mäkinen, Enni (My University, 2022)
Digitalization, the increasing use of information technology, is a topical phenomenon that has a strong impact on our society. Digitalization has had a particular impact on companies, as it offers new solutions and business models, but also new challenges to meet the rapid development of technology. Based on previous research data, the level of digitalization in Finnish companies can be considered good, but goals for its development and improvement have been presented. Based on previous research data, the state of digitalization in region of South Ostrobothnia is below the national level, which is why it is important to provide up-to-date research data on the topic. The aim of the study is to provide up-to-date research information on the role of digitalization in South Ostrobothnian companies and to increase the visibility of the topic. In addition to the role of digitalization, this study also examines servitization enabled by digitalization and the impact of digitalization on companies' operating environments, especially competition, networks and value creation. Servitization is approached as digital servitization, which means that digitalization is seen as an opportunity to offer new services and service models. This study is a qualitative study. The research material was collected by interviewing six digital companies of the year selected by the South Ostrobothnia Chamber of Commerce. The interviews were conducted as semi-structured thematic interviews. The interview was attended by people from companies with a strong knowledge of the company's digitalization. The findings of the study show that the role of digitalization in companies is significant, as it has streamlined existing or enabled entirely new business models. Digitalization is seen as a fundamental part of the company's operations and a strategically important factor. Attitudes towards digitalization are particularly positive and strong on the part of management. The study showed that digitalization enables servitization with different digital tools and channels, but the role of servitization was seen to grow more in the future. From business environment perspective, the study showed that digitalization has impact on competition, but the effects on value creation or the network model were still small.

Digitalisaatio eli lisääntyvä tietotekniikan hyödyntäminen on ajankohtainen ilmiö, joka vaikuttaa yhteiskuntaamme vahvasti. Digitalisaatio on vaikuttanut etenkin yritysten toimintaan, sillä se tarjoaa uusia ratkaisuja ja liiketoimintamalleja, mutta myös uusia haasteita vastata teknologian nopeaan kehitykseen. Suomalaisissa yrityksissä digitalisaation tasoa voidaan pitää aikaisemman tutkimustiedon perusteella hyvänä, mutta tavoitteita sen kehittämiseen ja parantamiseen on asetettu. Etelä-Pohjanmaan alue on aikaisemman tutkimustiedon perusteella kansallista tasoa alhaisemmalla tasolla digitalisaation hyödyntämisessä, minkä vuoksi aiheen esillä pitäminen ja ajantasaisen tutkimustiedot tuottaminen on tärkeää. Tutkimuksen tavoitteena on tuottaa ajantasaista tutkimustietoa eteläpohjalaisten yritysten digitalisaatiosta ja lisätä aiheen näkyvyyttä. Tämä tutkimus tarkastelee digitalisaation roolin lisäksi myös digitalisaation mahdollistamaa palveluistumista sekä digitalisaation vaikutusta yritysten toimintaympäristöön, etenkin kilpailuun, verkostoihin sekä arvonluontiin. Palveluistumista lähestytään digitaalisena palveluistumisena, eli digitalisaation nähdään mahdollistavan uusien palveluiden ja palvelumallien luomisen. Tämä tutkimus on laadullinen eli kvalitatiivinen tutkimus. Tutkimusaineisto kerättiin haastattelemalla kuutta Etelä-Pohjanmaan kauppakamarin valitsemaa vuoden digitaalista yritystä. Haastattelut toteutettiin puolistrukturoituina teemahaastatteluina. Haastatteluun osallistui henkilöitä yrityksistä, joilla oli vahva tietämys yrityksen digitalisaatiosta. Tutkimuksen löydökset osoittavat, että digitalisaation rooli tutkittavissa yrityksissä on merkittävä, sillä se on tehostanut olemassa olevia, tai mahdollistanut täysin uusia liiketoimintamalleja. Digitalisaatio nähtiin yrityksissä perustavanlaatuisena osana yrityksen toimintaa ja strategisesti merkittävänä tekijänä. Suhtautuminen digitalisaatioon on etenkin johdon puolelta positiivista ja vahvaa. Tutkimus osoitti, että digitalisaatio mahdollistaa yritysten palveluistumisen erilaisilla digitaalisilla työkaluilla ja kanavilla, mutta palveluistumisen rooli nähtiin kasvavan tulevaisuudessa enemmän. Tutkimuksessa kävi ilmi, että yritysten liiketoimintaympäristön kannalta digitalisaatio on vaikuttanut etenkin kilpailuun, mutta ilmiön vaikutukset arvonluontiin tai verkostomalliin nähtiin ainakin vielä vähäisinä.
Keywords: digitalisation; business; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development